(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
One of the most common types of pollution that has a negative impact on the biotic community in aquatic habitats is heavy metal poisoning of the water. Both essential and non-essential heavy metals can be toxic to living things if their concentrations are too high for their bioavailability. Although the toxicity of heavy metals, and especially anionic metal ions, is better known than that of cationic metal ions, it is just as toxic, if not more so. The focus of this review is on the usefulness of eukaryotic organisms like yeast, Saccharomyces cerevisiae, for toxicity assessment because they can be easily maintained and developed in controlled circumstances, thereby avoiding variability issues that arise when employing more complex organisms. Recent research has shown that the majority of cellular MTT reduction occurs outside of the mitochondrial inner membrane, and that this reduction is dependent on NADH and NADPH but is resistant to respiratory chain inhibitors.